Oral Rifampicin 300mg in Central Serous Chorioretinopathy(CSCR): Doi: 10.36351/pjo.v41i2.1754 - Haider, Muhammad Ali; Usman, Nida; Sattar, Uzma (Pakistan Journal of Ophthalmology, 2025)
This study evaluated the effectiveness of half-dose (300 mg) oral rifampicin in improving visual outcomes and reducing central macular thickness (CMT) in patients with idiopathic central serous chorioretinopathy (CSCR). Ten eyes from 10 patients who met the inclusion criteria were recruited by convenient sampling. Baseline visual acuity (VA) on the LogMAR chart and CMT measured via OCT were recorded. Patients received 300 mg rifampicin daily for six weeks, after which changes in VA and CMT were analyzed. Results showed significant improvements, with mean VA improving from 0.6±0.2 to 0.29±0.1 and mean CMT reducing from 556.5±15 µm to 262±60 µm. The mean reduction in CMT was 293±130 µm, and the improvement in VA was 0.32±0.2, both statistically significant (p ≤ 0.05). This study suggests that half-dose rifampicin is effective for CSCR treatment, offering a safer alternative with reduced side effects compared to full-dose therapy.